2007
DOI: 10.1007/978-3-540-75256-1_50
|View full text |Cite
|
Sign up to set email alerts
|

Independence Decomposition in Dynamic Bayesian Networks

Abstract: Abstract. Dynamic Bayesian networks are a special type of Bayesian network that explicitly incorporate the dimension of time. They can be distinguished into repetitive and non-repetitive networks. Repetitiveness implies that the set of random variables of the network and their independence relations are the same at each time step. Due to their structural symmetry, repetitive networks are easier to use and are, therefore, often taken as the standard. However, repetitiveness is a very strong assumption, which no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Boyen et al (1999) looked at a way of using SEM in learning DBNs and in particular found a novel approach to detecting hidden variables in dynamic systems. And while DBNs are generally constant over time, it is possible to learn DBNs that change as time progresses (Flesch & Lucas, 2007;Robinson & Hartemink, 2009) and indeed learn DBNs from non-temporal data (La¨hdesma¨ki & Shmulevich, 2008). Murphy and Mian (1999) show how DBNs subsume many other dynamic models into a general framework and look at the various tasks that need to be done to learn a DBN.…”
Section: Dynamic Bayesian Networkmentioning
confidence: 99%
See 3 more Smart Citations
“…Boyen et al (1999) looked at a way of using SEM in learning DBNs and in particular found a novel approach to detecting hidden variables in dynamic systems. And while DBNs are generally constant over time, it is possible to learn DBNs that change as time progresses (Flesch & Lucas, 2007;Robinson & Hartemink, 2009) and indeed learn DBNs from non-temporal data (La¨hdesma¨ki & Shmulevich, 2008). Murphy and Mian (1999) show how DBNs subsume many other dynamic models into a general framework and look at the various tasks that need to be done to learn a DBN.…”
Section: Dynamic Bayesian Networkmentioning
confidence: 99%
“…More information of DBNs can be found in the papers of Dean and Kanazawa (1989) and Friedman et al (1998) and in the work of Murphy and Mian (1999). In addition, Ghahramani (1998) examines the topic from the perspective of learning and Flesch and Lucas (2007) consider DBNs where the transition network can change over time. Learning Bayesian networks: approaches and issues…”
Section: Dynamic Bayesian Networkmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition Murphy and Mian (Murphy & Mian, 1999) show modeling of data using DBN. Ghahramani (Ghahramani, 1998) examines the topic from the perspective of learning and Flesch and Lucas (Flesch & Lucas, 2007) consider DBNs where the transition network can change over time.…”
Section: Dynamic Bayesian Networkmentioning
confidence: 99%